The effects of anti-IL-10 and anti-TGF? on conception rates in mice - Risvanli, A.; Godekmerdan, A. (Wiley-Blackwell, 2012)
[Abstract Not Available]
16th Annual Conference of the European-Society-for-Domestic-Animal-Reproduction (ESDAR) -- AUG 29-SEP 01, 2012 -- Univ Coll Dublin (UCD), Befield Campus, UCD Vet Sci Ctr, Dublin, IRELAND